Badanie Niektórych Własności Strukturalnych Górotworu Metodą Akustyczną - Kołtoński, W. (Engineering Transactions, 1965)
The present needs of drilling and mining geophysics necessitated some theoretical and experimental research concerning the application of elastic waves for the determination of certain properties of a rock mass. These properties are connected with the degree of porosity of sandstone or sand at various temperatures and various states of liquid saturation.The choice of elastic waves as a means for the research is not accidental and follows from the results of earlier scientific works in which certain direct relations were detected between the degree of porosity of a solid and the propagation velocity and damping of the elastic wave in that medium.The present work is a tentative application of these relations to practical problems and their experimental verification. In view of definite geophysical purposes all the considerations and experiments are confined to two particular types of rock mass (sands and sandstones) and to longitudinal waves with frequencies lying near the boundary of the audible and the ultrasonic range.In the first part of the work is presented a computation method based on the theories of Biot and Brandt, for the velocity and damping of an elastic wave in porous rock mass at various states of liquid saturation and in the temperature range from 5 to 100°C. In the second part the computation of the same wave parameters in the negative temperature range is discussed. A number of computation examples are given, for which the results are confronted with those of experimental investigation, showing satisfactory agreement.The third part of the paper contains a description of the measurement methods and devices and a summary of the experimental-laboratory and obtained in the field results. Finally, the author shows some possibilities of application to the acoustical velocity logging of bore-holes and testing a freezing cloak applied a in pit shafts constructing.